MULTILITERACY EDUKIT IN ELEMENTARY SCHOOLS: PERCEIVED USEFULNESS, EASE OF USE, CURRICULUM FIT, SCHOOL SUPPORT, AND BEHAVIORAL INTENTION IN INDONESIA–MALAYSIA - Indra Suhendra; Tatat Hartati; Muhammad Ikhwan Nugraha; Ira Rengganis; Effy Mulyasari; Dudu Suhandi Saputra (Universitas Majalengka, 2026)
The multiliteracy Edukit integrates reading, writing, critical thinking, and authentic production into a single elementary classroom session. Purpose: To compare Indonesian and Malaysian elementary teachers’ perceptions across five acceptance dimensions: Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Curriculum Fit (CF), School Support (SS), and Behavioral intention (BI). Methods: A comparative survey of 30 teachers (Indonesia n=15; Malaysia n=15) used a validated 22 item, five point Likert questionnaire; per dimension reliability was adequate (α≥0.70). Mann–Whitney tests were applied to each indicator with effect size r reported. Results: Indonesian teachers scored higher across all dimensions, with 17 of 22 indicators significantly different (p<0.05). PEOU was the strongest discriminator (r≈0.60), followed by CF (r≈0.52), and SS showed the smallest difference (r≈0.32). The findings indicate that curriculum context and institutional support shape teachers’ acceptance of Edukit. Conclusion: Acceptance was driven by ease of use, curriculum alignment, and school support. Implementation strategies must align with the characteristics of Indonesia’s Kurikulum Merdeka and Malaysia’s KSSR. Implications: Strengthening training, aligning teaching/assessment artefacts, and ensuring access to simple materials are necessary to sustain adoption. Limitations: small, perception based sample; future studies should expand the sample and assess the impact on student outcomes.